Aetiology and antibiotic susceptibility of bacterial keratitis at a referral centre in southern Sweden - Elin Österhed; Karl Oldberg; Ingemar Gustafsson (Scientific Reports)
Abstract This was a retrospective cross-sectional study evaluating the aetiology and antibiotic susceptibility in patients treated for suspected bacterial keratitis at Skåne University Hospital during 2019. Inclusion criteria: eyes with bacterial keratitis. Exclusion criteria: co-infection with other microbes. Primary outcome parameters: predisposing factors, causative pathogens and antibiotic susceptibility. Secondary outcome parameter: antibiotic treatment. A total of 255 cases met the inclusion criteria. Of these, 149 (58%) occurred in contact lens wearers. Corneal cultures, when performed, were positive in 51% of cases. For eyes which had received antibiotic treatment prior to corneal culture (n = 36), the proportion of positive cultures was 50%. Ulcers < 1 mm were less likely to yield a positive culture than those ≥ 1 mm. The most frequently isolated bacteria were coagulase-negative staphylococci (48%). Antibiotic resistance rates were lowest to levofloxacin (0%), ciprofloxacin (2%) and chloramphenicol (4%), and highest to fusidic acid (47%) and clindamycin (19%). The low proportion of positive cultures from small ulcers suggests that these warrant a different diagnostic approach. Furthermore, corneal cultures from eyes with ongoing antibiotic treatment were positive to the same extent as those from untreated eyes, suggesting that discontinuation of antibiotic treatment before re-culturing might not be necessary.